2020
DOI: 10.1002/cbic.202000541
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Conformation States of Neurotensin Receptor 1 Variants by NMR Site‐Directed Methyl Labeling

Abstract: G protein‐coupled receptors (GPCRs) are key players in mediating signal transduction across the cell membrane. However, due to their intrinsic instability, many GPCRs are not suitable for structural investigations. Various approaches have been developed in recent years to remedy this situation, ranging from the use of more native membrane mimetics to protein‐stabilization methods. The latter approach typically results in GPCRs that contain various numbers of mutations. However, probing the functionality of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…R149 3.32 is linked to TM2 via a salt bridge with E124 2.61 and to TM7 via a cation- interaction with F358 7.42 . In a recent nuclear magnetic resonance (NMR) study on NTSR1-H4, it was shown that the mutation E124 2.61 D, which weakens the interaction with R149 3.32 , stabilizes the active state of the receptor (50). In agreement, the mutations R149 3.32 M and F358 7.42 A result in increased affinity for NTS [8][9][10][11][12][13] (Fig.…”
Section: Interhelical Polar Network and Hydrophobic Core In Ntsr1 Actmentioning
confidence: 73%
See 1 more Smart Citation
“…R149 3.32 is linked to TM2 via a salt bridge with E124 2.61 and to TM7 via a cation- interaction with F358 7.42 . In a recent nuclear magnetic resonance (NMR) study on NTSR1-H4, it was shown that the mutation E124 2.61 D, which weakens the interaction with R149 3.32 , stabilizes the active state of the receptor (50). In agreement, the mutations R149 3.32 M and F358 7.42 A result in increased affinity for NTS [8][9][10][11][12][13] (Fig.…”
Section: Interhelical Polar Network and Hydrophobic Core In Ntsr1 Actmentioning
confidence: 73%
“…Data were normalized to the response of 10 M NTS 8-13 and are shown as means ± SEM from 3 to 11 independent experiments performed in duplicate. EC 50 with the ability to mimic the binding mode of the endogenous peptide agonist NTS. Last, the helical and side-chain rearrangements observed in the extracellular receptor half, in combination with functional data, provide detailed insights into the transmission of the activation trigger to the cytosolic side through a polar network and an aromatic cluster beneath the agonist pocket.…”
Section: Introductionmentioning
confidence: 99%
“…[58]), electron paramagnetic resonance (EPR) (reviewed in Refs [59,60]), and fluorescence spectroscopy (reviewed in Refs [61,62]) supported by molecular dynamics (MD) simulations (reviewed in Refs [63,64]) have been used in complementation to crystallographic and cryo-EM studies to analyze different conformational states of GPCRs and to determine their liganddependent energetics and rates of interconversion. Several NMR studies on the b 1 and b 2 adrenergic receptors (b 1 AR and b 2 AR) [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], the adenosine A 2A receptor (A 2A R) [81][82][83][84][85][86][87], the l-opioid receptor (lOR) [88,89], the leukotriene B 4 receptor 2 (BLT2R) [90], the a 1A adrenergic receptor (a 1A R) [91], the neurotensin receptor type 1 (NTSR1) [92], and the M 2 R [93,94] have shown that GPCRs are highly dynamic proteins that exist in an equilibrium between multiple functionally relevant conformational states. Among these receptors, the b 2 AR and the A 2A R are the most extensively studied GPCRs in terms of their conformational dynamics.…”
Section: Ligand-dependent Conformational Dynamics Of the Intracellulamentioning
confidence: 99%
“…MMTS labeling was done according to a published protocols [29] with specific modifications required for a membrane protein [30]. After chromatographic separation by a semipreparative S200 (300/10) column the pooled fractions were concentrated in Amicon 15 centrifugal devices (10,000 MWCO) to approx.…”
Section: Cysteine-specific Methyl Labeling With S-methyl-methanethios...mentioning
confidence: 99%